Microstructural effects on the single crystal diamond tool wear in ultraprecision turning of Ti6Al4V alloys. (January 2023) - Zhao, Zejia; Fu, Yexiang; To, Suet; Zhang, Guoqing; Lin, Jianjun
Abstract: Single crystal diamond tools are common cutters in the ultraprecision machining, but the tool wear is a great concern in machining of difficult-to-cut materials. In this paper, material microstructural effect on the diamond tool wear is firstly investigated in ultraprecision turning of difficult-to-cut Ti6Al4V alloys. Equiaxial, bimodal and lamellar microstructures are used in the machining. Results show that more adhesion of Ti6Al4V workpiece is observed at the flank face instead of the rake face in turning of all types of microstructures. The tool wear in turning of the lamellar alloy is less than that of the equiaxial and bimodal alloys, giving rise to low cutting forces and high surface quality. Furthermore, discontinuous serrated chips are observed for the equiaxial and bimodal alloys at the cutting distance of 3000 m, while the chips remain continuous in machining of the lamellar martensitic alloys. Besides, the diamond tool wear mechanism is discussed from perspectives of tool wear modes and chemical reactions by characterizations of the scanning electron microscope, atomic force microscope atom, X-ray photoelectron spectra and high-resolution transmission electron microscope. This study aims to clearly understand the diamond tool wear mechanism in ultraprecision machining of the Ti6Al4V alloys. Graphical abstract: Unlabelled Image Highlights: Microstructural effect on the tool wear is firstly studied in UT of Ti6Al4V alloys. Lamellar microstructure gives rise to small diamond tool wear rate. Different wear rates is due to the crystal anisotropy of the rake and flank faces. Craters and flank wear land are the main wear modes of the diamond tool. Chemical reactions in the UT are confirmed via XPS and HRTEM measurement.